PERAMALAN PENYEDIAAN JUMLAH VAKSIN UNTUK BALITA DENGAN METODE SINGLE EXPONENTIAL SMOOTHING DI DINAS KESEHATAN KABUPATEN ASAHAN - Moekti, Hadhysti Aulia Hadhysti; Ramdhan, William; Syaputra, Abdul Karim (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
Requests for vaccines for toddlers from the Asahan District Health Service are currently still considered to be less effective. There is still often an excess of vaccine procurement (overstock) which results in a buildup of vaccines in storage, increasing the risk that the vaccine will not last long or expire and if the number of immunization vaccines is reduced, there will be a shortage of vaccine stock for toddlers. There is no process for calculating the number of vaccines needed, so it is often wrong to estimate the number of vaccines needed for toddlers. So currently the vaccine stock is not yet stable at the Asahan District Health Service. This is a problem at the Asa-han District Health Service, so a forecasting system is needed to calculate vaccine stock every following month. To overcome this problem, it is necessary to carry out forecasting to find out a situation in the future using past data which can help the running of a company's activities, especially so that the stock of vaccines for toddlers remains stable. One effective method for forecasting is the Single Exponential Smoothing (SES) method.